Konsep Perkuliahan Daring Google Classroom dalam Meningkatkan Interaksi Akademik Di Tengah Pandemi Korona - Wildah Nurul Islami; Sholihudin Al Ayubi (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2020)
Google classroom online education concept in increasing academic interaction in the middle of the pandemi of corona. The outbreak of the co-19 pandemic requires lecturers and students to carry out online learning as opportunities and challenges, including through Google classroom. This research is a qualitative research to describe the concept of online lectures through Google classroom in improving academic interaction in the middle of a corona pandemic. The concept of this lecture is a design that shows strategic steps to improve academic interaction between lecturers and students. The subjects of this study were 100 students of STAI Ar-Rosyid. Data collection techniques through documentation (odd semester course schedules, class lists, student attendance online attendance, syllabus and RPS, student learning outcomes) were analyzed using qualitative descriptive methods. In the concept of online lectures, lecturers must prepare a planned design in the form of a Google classroom learning implementation mechanism. The researcher determines two tasks namely the task of making PPT presentation videos and summarizing the results of the discussion. The task of the lecturer is not only to monitor lectures when learning lasts until the end, but there must be an evaluation and review for improvement in the next meeting. This is a form of academic interaction between lecturers and students.